Novel TIE‐2 inhibitor BAY‐826 displays in vivo efficacy in experimental syngeneic murine glioma models. Issue 1 (12th December 2016) - Schneider, Hannah; Szabo, Emese; Machado, Raquel A. C.; Broggini‐Tenzer, Angela; Walter, Alexander; Lobell, Mario; Heldmann, Dieter; Süssmeier, Frank; Grünewald, Sylvia; Weller, Michael
Abstract : Our data in syngeneic murine glioma models demonstrate that TIE‐2 kinase inhibition, using a novel, highly potent and orally available small molecule inhibitor (BAY‐826), may improve benefit from the efficacy of radiotherapy in highly vascularized tumors such as glioblastoma. Abstract: Targeting the vascular endothelial growth factor signaling axis in glioblastoma inevitably leads to tumor recurrence and a more aggressive phenotype. Therefore, other angiogenic pathways, like the angiopoietin/tunica interna endothelial cell kinase (TIE) signaling axis, have become additional targets for therapeutic intervention. Here, we explored whether targeting the receptor tyrosine kinase TIE‐2 using a novel, highly potent, orally available small molecule TIE‐2 inhibitor (BAY‐826) improves tumor control in syngeneic mouse glioma models. BAY‐826 inhibits TIE‐2 phosphorylation in vitro and in vivo as demonstrated by suppression of Angiopoietin‐1‐ or Na3 VO4 ‐induced TIE‐2 phosphorylation in glioma cells or extracts of lungs from BAY‐826‐treated mice. There was a trend toward prolonged survival upon single‐agent treatment in two of four models (SMA‐497 and SMA‐540) and there was a significant survival benefit in one model (SMA‐560). Co‐treatment with BAY‐826 and irradiation was ineffective in one model (SMA‐497), but provided synergistic prolongation of survival in another (SMA‐560). Decreased vessel densities and increased leukocyte infiltration were observed, but might be independent processes as the effect was also observed in single treatment modalities. These data demonstrate that TIE‐2 inhibition may improve tumor response to treatment in highly vascularized tumors such as glioblastoma.